Conjugated Polymer as Health Biosensor - Siti Amira Othman (Multidisciplinary Applied Research and Innovation, 2023)
In this scope of the study, the research is focused on the conductive polyaniline characterization and properties. The pH level will be measured using a portable pH meter, and the temperature will be measured too using a thermometer. Next, the synthesis of polyaniline will use hydrochloric acid as the protonic acid and ammonium persulfate as the oxidation reagent. Synthesizing play an important role in this part of the research because more time synthesizes the polyaniline’s higher conductivity to achieve. The drying process is also important to produce powder from the synthesis of aniline solution, which is polyaniline emeraldine salt (green powder) and polyaniline emeraldine base (blue powder) will come out. The electrical conductivity of doped samples will be measured. The conductivity or electrical properties of the polyaniline film will be investigated. Data and analysis will be collected as the result.